Depresi sosial tokoh perempuan dalam kumpulan cerpen Jurig Paséa Jeung Nyi Karsih karya Tini Kartini (kajian sosiologi sastra Ian Watt) - Dewi, Gita Kurnia; Koswara, Dedi (Fakultas Bahasa Seni dan Budaya, 2023)
This study aims to analyze and describe: 1) the social background of Tini Kartini as a representative of the community group, 2) the social situation of depression that occurred in the community when the work was published, 3) the content of the text of the Jurig Paséa jeung Nyi Karsih short story collection which reflects the idea of depression, and 4) a social mirror from Jurig Paséa jeung Nyi Karsih's short story collection. The method used in this research is descriptive method. The results of this study, firstly, Tini Kartini's social background as a representative of community groups, meaning how the author's social background is related to the publication of the literary work. Second, the depressed social situation that occurred in society when the work was published, clearly existed during the Soekarno era. Third, there are four ideas of depression that occur in female characters in the short story